HUBUNGAN ANTARA PENGETAHUAN, SIKAP, DAN PERILAKU IBU MENGENAI PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT TERHADAP KEJADIAN DIARE PADA BALITA DI KELURAHAN SIANTAN TENGAH - ., Arianti Miranti Lestari Fajrin (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Backround: Diarrhea is one of public health problem in Pontianak.Sanitation, early complementary feeding, and not-exclussive breastfeedingcan affect the incidence of diarrhea in toddlers. Community-Led TotalSanitation (CLTS) program is a program to decrease the incidence ofdiarrhea by change the sanitation behavior in community. Objective: Thisresearch aimed to investigate the correlation between mothersknowledge, attitude, and behavior on CLTS program toward the toddlerssdiarrhea in Siantan Tengah district and to know the description ofbreastfeeding and complementary feedings characteristics.Methodology: This research was an observational analytic study withcross sectional design which has done to 100 mothers in Siantan Tengah.Chi Square test was used to analyze data. Results: Chi Square testshowed a significant correlation between mothers knowledge (p = 0.003) ,attitude (p = 0.000) , and behavior (p = 0.000) on CLTS program towardthe incidence of diarrhea in toddlers. Results also showed 17,6% oftoddlers got exclusive breastfeeding and 85.3% got early complementaryfeeding. Conclusion: There is a significant correlation between mothersknowledge, attitude, and behavior on CLTS program toward the toddlerssdiarrhea in Siantan Tengah district and almost of responden gave an earlycomplementary feeding and not-exclussive breastfeeding to their toddlers.Keyword: Community-led total sanitation, diarrhea, motherbehavior1) Medical School, Faculty of Medicine, University of Tanjungpura,Pontianak, West Borneo2) Department of Public Health, Faculty of Medicine, University ofTanjungpura, Pontianak, West Borneo3) Department of Pediatric, Faculty of Medicine, University ofTanjungpura, Pontianak, West Borneo